Emotional stability is associated with the MAOA promoter uVNTR polymorphism in women - Rodríguez‐Ramos, Ángel (Brain Behav, 2019)
BACKGROUND: Neuroticism is associated with low emotional stability, and it is characterized by a tendency to perceive ordinary situations as threatening and difficult to manage. This personality trait has been associated with psychological distress and predicts some mental disorders. Previous studies have shown that women tend to be more neurotic than men and, in general, females have also a higher incidence of anxious and depressive disorders. METHODS: We analyzed in a sample of 99 female university students (from 18 to 26 years old) if emotional stability, measured using the Big Five Questionnaire, was linked to polymorphic variants in candidate genes related to dopaminergic and serotonergic systems, and other personality variables. RESULTS: We found that emotional stability and its subdimensions are genetically associated with MAOA‐uVNTR polymorphism. Thus, women carriers of the 3‐repeat allele (lower MAO‐A expression) showed higher levels of emotional stability. No associations were found with other polymorphisms analyzed, including COMT Val(158)Met, 5‐HTTLPR, and DAT 3′UTR VNTR. Furthermore, our results showed a negative correlation between emotional stability and depression, state anxiety, and trait anxiety. In fact, MAOA‐uVNTR and trait anxiety also explained emotional stability and its subdimensions. We also found that other genetic characteristic, phenylthiocarbamide tasting, explained impulsivity, specifically tasters controlled impulses better than nontasters. CONCLUSION: Our results indicate that neuroticism might be regulated by MAOA and could be a common factor between different phenotypes, such as aggressive behaviors or personality disorders, observed in women with higher activity genotype who had been exposed to negative environments during childhood. This study could lead to a better understanding of the basis of emotional stability and could lead to future projects for this purpose.